A thermal emissions-based real-time monitoring system for in situ detection of fatigue cracks. (26th October 2022) - Amjad, K.; Lambert, P.; Middleton, C. A.; Greene, R. J.; Patterson, E. A.
Abstract : The advent of packaged infrared (IR) bolometers has led to thermography-based techniques becoming popular for non-destructive evaluation of aerospace structures. In this work, a real-time monitoring system for in situ crack detection has been presented which uses an original equipment manufacturer microbolometer. The system costs one-tenth the price of a packaged bolometer and has the potential to transform the use of IR imaging for condition and structural health monitoring in the aerospace industry and elsewhere. A computer, consisting of a single circuit board with dimensions comparable to a credit card, has been integrated into the system for real-time, on-board data processing. Crack detection has been performed based on the principles of thermoelastic stress analysis (TSA). Proof-of-concept laboratory tests were performed on open-hole aluminium specimens to compare the performance of the proposed system against a state-of-the-art cooled IR photovoltaic effect detector. It was demonstrated that cracks as small as 1 mm in length can be detected with loading frequencies as low as 0.3 Hz. This represents a significant advance in the viability of TSA-based crack detection in large-scale structural tests where loading frequencies are usually lower than 1 Hz.